(Table 2, Annex), Manganese crusts and manganese coated rocks recovered from study area (lat 26°N) - Peter A Rona; Reginald N Harbison; Bobby G Bassinger; Robert B Scott; Andrew J Nalwalk (PANGAEA, 1976)
An asymmetric tectonic fabric was delineated by narrow-beam bathymetric profiles in a 180-km2 area of the Mid-Atlantic Ridge crest at lat 26°N. Features of the tectonic fabric are a continuous rift valley offset by small (<10-km) transform faults and minor fracture zones expressed as valleys with intervening ridges that trend normal and oblique to the two sides of the rift valley. The discharge zone of a postulated sub-sea-floor hydrothermal convection system is focused by faults on the southeast wall of the rift valley and driven by intrusive heat sources beneath the rift valley. The rift valley has a double structure consisting of linear segments, bounded by ridges, and basins at the intersections of the minor fracture zones. The double structure of the rift valley acts like a template that programs the reproduction of the tectonic fabric. The minor fracture zones form an asymmetric V about the rift valley at variance with the symmetric small circles formed by major fracture zones. To reconcile the asymmetry of minor fracture zones with the symmetry of major fracture zones, it is proposed that the minor fracture zones have been preferentially reoriented by an external stress field attributed to interplate and intraplate motions. Major fracture zones remain symmetric under the same stress field owing to differential stability between minor and major structures of oceanic lithosphere.
Supplement to: Rona, PA et al. (1976): Tectonic fabric and hydrothermal activity of Mid-Atlantic Ridge crest (lat 26°N). Geological Society of America Bulletin, 87, 661-674, https://doi.org/10.1130/0016-7606(1976)87%3C661:TFAHAO%3E2.0.CO;2